(3ebOeI aj GdGbJUGO GdbjGSj (B/s - (3YHO GdQMef, YHO GdeMehO eMeO s ((3GdQjGV (B: s (3LGeYI Gdedc SYhO(B, s, 1995)
(3jgJe HOQGSI fehPL GdGfMOGQ GdNWj, GdfehPL GdNWj deJZjQjf Ch GdGfMOGQ GdHSjW hGdfehPL GdNWj GdYGe Ch GdGfMOGQ GdeJYOOI, jJfGhd GdeTcdGJ GdbjGSjI aj fehPL GdGfMOGQ GdGQJHGW GdNWj GdeJYOO, GNJdGa GdJHGjf hGdGQJHGW GdPGJj GdeJZjQGJ GdeJHGWFI, ehVhYGJ aj GdGbJUGO GdbjGSj hfeGPL GdeYGOdGJ GdBfjI haj GdCNjQ eQGMd GdHMK GdbjGSj GdJWHjbj(B.s
(3GdedGMb U(B.425 (3HjHdjhZQGajG(B: (3U U(B485-491 (3cTGa eUWdMGJ U(B.493s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdJMdjdjs; (3GdGbJUGO GdQjGVjs